2015
DOI: 10.5007/2175-8069.2015v12n27p27
|View full text |Cite
|
Sign up to set email alerts
|

Insolvência empresarial: um estudo sobre as distribuidoras de energia elétrica brasileiras

Abstract: O objetivo deste trabalho é descobrir quais são os indicadores financeiros e operacionais mais relevantes para a explicação da insolvência no setor de distribuição de energia elétrica no Brasil. Além da grande relevância do setor para a economia brasileira, recentemente a Agência Nacional de Energia Elétrica emitiu a Nota Técnica nº 353/2014 visando criar mecanismos de acompanhamento constante da sustentabilidade econômico-financeira dessas distribuidoras. Para o estudo, foi utilizada a técnica de regressão lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
3
5
0
3
Order By: Relevance
“…The most important indicators in terms of average impact on efficiencies and densities were consistent with results of Scalzer et al (2015), who identified Y 3 (Actual EFP /Regulatory EFP) as the most important insolvency indicator in the year of the event. In addition, the ex-ante definition of insolvency based on negative Shareholders' Equity/Assets (Wruck 1990) uses an indicator that has a correlation of -0.98 with Y 1 (Overall Indebtedness), i.e., the same indicator with opposite sign.…”
Section: Variables That Explain Insolvencysupporting
confidence: 84%
See 4 more Smart Citations
“…The most important indicators in terms of average impact on efficiencies and densities were consistent with results of Scalzer et al (2015), who identified Y 3 (Actual EFP /Regulatory EFP) as the most important insolvency indicator in the year of the event. In addition, the ex-ante definition of insolvency based on negative Shareholders' Equity/Assets (Wruck 1990) uses an indicator that has a correlation of -0.98 with Y 1 (Overall Indebtedness), i.e., the same indicator with opposite sign.…”
Section: Variables That Explain Insolvencysupporting
confidence: 84%
“…As seen previously, Y 4 is the average of Y 2 and Y 3 , and thus Y 3 's information remains in Y 4 . The results of sensitivity analysis I are also in line with Scalzer et al (2015), who also found that Y 8 (Overall Liquidity) was important when analyzing insolvent EDs. The sensitivity analysis II showed that no other variable was significant in changing ED efficiencies.…”
Section: Robustness Analysissupporting
confidence: 78%
See 3 more Smart Citations